Audio Content: the Use of Podcast as an Educational Resource in Histology Subject - Tosta, Sofia (2022)
Increased use of online tools and digital media along with the speed in which information becomes available over the last few years, asks for adaptations on the educational environments. Recently, due to restrictions imposed by the Covid-19 pandemic, the world has witnessed profound changes in the educational scenario, with a real disruption in the teaching-learning process, which has forcibly been mediated by digital interfaces. In the present work, an experience will be presented, within the scope of education carried out in other classrooms, and also carried out in a Dentistry course at a Brazilian public university. A podcast, with 20 episodes, was implemented as a complementary educational resource, in the Histology discipline. The podcast was made available on the Spotify platform and associated with an Instagram account for dissemination and placement of materials, such as summaries and photos from the course's slide bank. At the end of the school year, a form had been sent to assess the perception of students that listened to the podcast. The project reached 1,262 people, including 14 foreigners. From 87 participants who answered the form, 89.7% noticed a great improvement in their subject understanding and 96.6% rated the content as excellent. The results bring a successful experience during emergency remote teaching, reinforcing the possibility of adopting new digital technologies, which can privilege distant activities and with the potential to generate greater engagement and autonomy for students. Keywords: Learning. Technology. Podcast. Histology.